Pengembangan Modul IPA/Fisika Terpadu Berbasis Scaffolding pada Tema Gerak Untuk Siswa Kelas VIII SMP/MTs - Budaeng, Jumaidin; Ayu, Hena Dian; Pratiwi, Hestiningtyas Yuli (Momentum: Physics Education Journal, 2017)
This research aims to develop the Integrated Science Module Based on Scene Motion Scaffolding, knowing the quality of Integrated Science module, and evaluate the response of teachers and students of the Integrated Science module. This study is a research and development (R & D) by Borg and Gall modified by Sugiyono. The results of the research module Integrated Science for students developed by subject matter experts and media experts have a quality percentage of each 85% (excellent) and 86.6% (excellent). While the modules for teachers according to subject matter experts and media experts have quality with the percentage of each 84% (excellent) and 87% (very good), the response of teachers to the teacher module and student module is Strongly Agree with the percentage of each 87.5 % and 89.84%. Of the 10 students of SMP Negeri 3 Kepanjen on a limited test, got the students' response to student IPA module is Strongly Agree with the percentage of 85%. It can be concluded that the Integrated Science Module Based on Scene Motion Scaffolding has met the criteria Very Good quality and fit for use as a teaching material Integrated Science for students of class VIII SMP/MTs.Keywords: Integrated Science Module, Scaffolding, MotionÃ‚Â Penelitian ini bertujuan untuk mengembangkan Modul IPA Terpadu Berbasis Scaffolding pada Tema Gerak, mengetahui kualitas modul IPA Terpadu, dan mengetahui respon guru dan siswa terhadap modul IPA Terpadu. Penelitian ini merupakan penelitian dan pengembangan (R&D) menurut Borg dan Gall yang dimodifikasi oleh Sugiyono. Hasil penelitian modul IPA Terpadu untuk siswa yang dikembangkan menurut ahli materi dan ahli media memiliki kualitas persentase masing-masing 85% (sangat baik) dan 86,6% (sangat baik). Sedangkan modul untuk guru menurut ahli materi dan ahli media memiliki kualitas dengan persentase masing-masing 84% (sangat baik) dan 87% (sangat baik), respon guru terhadap modul guru dan modul siswa adalah Sangat Setuju dengan persentase masing-masing 87,5% dan 89,84%. Dari 10 siswa SMP Negeri 3 Kepanjen pada uji terbatas, mendapat respon siswa terhadap modul IPA siswa adalah Sangat Setuju dengan persentase 85%. Dengan demikian dapat disimpulkan bahwa Modul IPA Terpadu Berbasis Scaffolding pada Tema Gerak telah memenuhi kriteria kualitas Sangat Baik dan layak digunakan sebagai salah satu bahan ajar IPA Terpadu untuk siswa kelas VIII SMP/MTs.Kata Kunci: Modul IPA Terpadu, Scaffolding, Gerak